The More (Social Group Memberships), the Merrier: Is This the Case for Asians? - Chang, Melissa X.-L.; Jetten, Jolanda; Cruwys, Tegan; Haslam, Catherine; Praharso, Nurul (Frontiers in Psychology, 2016)
While previous studies have consistently shown that belonging to multiple groups enhances well-being, the current research proposes that for Asians, multiple group memberships (MGM) may confer fewer well-being benefits. We suggest that this is due, in part, to Asian norms about relationships and support seeking, making Asians more reluctant to enlist social support due to concerns about burdening others. Overall, MGM was associated with enhanced well-being in Westerners (Study 2), but not Asians (Studies 1, 2, 3). Study 2 showed that social support mediated the relationship between MGM and well-being for Westerners only. In Study 3, among Asians, MGM benefited the well-being of those who were least reluctant to enlist support. Finally, reviewing the MGM evidence-base to date, relative to Westerners, MGM was less beneficial for the well-being of Asians. The evidence underscores the importance of culture in influencing how likely individuals utilize their group memberships as psychological resources.